Employer attractiveness in Nordic Europe - Minelgaite, Ina; Guðmundsdóttir, Svala; Jóhannsdóttir, Lára; Larsen, Nathalie Nørregaard; Ólafsson, Snjólfur; Richter, Nicole Franziska (Springer, 2021)
The five Nordic nations and three autonomous territories, clustered together, make up the 11th largest economy in the world, with 27 million inhabitants and ranking high, regionally and globally, regarding many measures of well-being, gender equality, university-level education, and financial affluence. Nordic nations value highly sustainable development and have agreed upon sustainable development indicators. This chapter presents findings from two Nordic nations, Denmark and Iceland, respectively, but make an interesting comparison since one is a fairly populated, located in mainland Europe and a member of the European Union, while the other is a sparsely populated, non-European Union nation, located in the middle of the Atlantic Ocean. The GLOBE research has, with regards to factors such as language, history, religion, and technological development, categorized both Denmark and Iceland within a Nordic-cluster group. Other common factors are welfare state models, common history, and culture. The hierarchical differences are small within organizations, where decentralized and democratic characteristics distinguish the management of employees. With regards to CSR and competitiveness of Nordic businesses long-term sustainability is emphasized and international co-ordination, such as by promoting and implementing international standards, policy-frameworks, and guidelines.